A Review of Leadership and Organizational Performance - Pushpanathan, A. (Vavuniya Campus of the University of Jaffna, 2008)
For many years the assumption that leaders influenced organizational performance went challenged. Theorists approached the study of leadership assuming that leaders contributed significantly to the organizational effectiveness. Most researchers evaluate leadership effectiveness in terms of the consequences of the leader’s actions for followers and other organization stakeholders. From the review, it was observed that many researches were done on leadership approaches, out of which a fair number of researches were done in relation to the organizational performance. The researches, which correlate the leadership styles and organizational performance, are having different coverage areas. Those researches considered the whole public sector or whole private sector or the both the sectors as a whole. Many different types of outcomes have been used, including the performance and growth of the leader’s group or organization, its preparedness to deal with challenges or crises, follower satisfaction with the leader, follower commitment to the group objectives, the psychological well-being and development of followers, the leader’s retention of high status in the group, and the leader’s advancement to higher positions of authority in the organization. This study analysis the review of literature from different authors based on leadership and organizational performance.
Keywords: Leadership; Organization; Performance